Genetic diversity and stability in starch physicochemical property traits of potato breeding lines. (30th August 2019) - Ahmed, Sulaiman; Ru, Weidong; Cheng, Linrun; Bian, Xiaobo; Zhang, Liang; Jin, Liping; Bao, Jinsong
Highlights: Starch properties for 206 F1 clones were screened according to AAC, PV and Tp. Twenty lines with high/low AAC, PV and Tp were selected. These lines displayed a relative stability across different environment (location). HP-206 line showed relatively higher AAC (32.6 and 29.2%) in two locations. HP-37 line gave high PV (478.0 and 486.8 RVU) in two locations. Abstract: Cross breeding may create wider genetic variation than two parents used in hybridization, but breeding efforts towards starch quality improvement are less reported in potato. A cross was made between Zhongshu-3 and Favorita to select desired starch properties in progenies. Among 206 F1 clones with potential high yield, starch qualities such as apparent amylose content (AAC), pasting viscosity, and thermal properties were further evaluated. A wide variation was observed in different starch physicochemical indices for 206 potato accessions. Twenty clones with high/low AAC, peak viscosity and peak gelatinization temperature were selected and then grown at another location to evaluate the stability of the traits. Similar wide range of variation in the starch properties was observed. Cluster analysis based on starch properties of the 20 selected clones indicating relative stability of the starch property traits across different locations. New breeding lines identified have potential for application in food and other industries.